(untitled) (ACME, 2023)
This paper deals with John Chrysostom’s homily Quod frequenter conveniendum sit (CPG 4441.03). In particular, the aim of the article is the publication of the critical text, for the first time ever, of a section of the homily that is missing in the ms. Ott. gr. 431 – used by Bernard de Montfaucon to accomplish the first edition of the Undecim novae homiliae which this manuscript transmits – since the f. 171 fell. Thanks to the discovery of the ms. Stavronikita 6, which took place in the mid-1950s, it is now possible to fulfill the gap of the ottobonianus manuscript, because the Mount Athos’ codex conveys the same homilies’ series providing however the complete text where that of the Vatican is lacking. This work is therefore composed of the critical text of the excerpt so far unpublished, the corresponding italian translation and some commentary notes.